PENGARUH KOREKSI FISKAL ATAS LAPORAN LABA RUGI KOMERSIAL TERHADAP PENGHASILAN KENA PAJAK - Tony S. Chendrawan (Jurnal Ekonomi-Qu, 2017)
Company as corporation which become corporate of tax subject has the duty of reporting all of its activities which are related to taxation to the tax imposed in accordance with the prevailing of the determination and taxing legislation. In order not to giving the wrong information on estimating the company potential on outcome the income after tax, first of all, it should be doing reconciliation or adjustment the financial report with the admission of revenue and expense determination which those based on Standar Akuntansi Keuangan (SAK), because not always same as The Determination Rules of  Taxing Legislation , so it will cause a differentation between commercial financial report with fiscal financial report. For that, it must be doing a tax adjustment.According to Mohammad Zein (2005:202-208), differentiation that was happened between income before tax and taxable income, caused by permanent difference and timing difference. If that tax adjustment  is resulting the fiscal profit bigger than the commercial profit, is called a positive of tax adjustment, but if the fiscal profit become less than the commercial profit is called a negative of tax adjustment. This research is focused to identify: (1) How the influence of the tax adjustment on commercial income statement partially to taxable income (2) How the influence of the tax adjustment on commercial income statement simultaneously to taxable income.The method used on this research is Descriptive and Verificative. The objective are the LQ 45 company which are listed on  Bursa Efek Jakarta (BEJ). Sampling technique used is the Purposive Sampling method, acquired  19 sample from 45 company of  LQ 45.  To solve this research briefly use by Multiple Regression model formula by SPSS for Windows 10.0 program. Before that, the test on Classical Assumption, that is concist of Multicoloniearity test, Autocorrelation test, Heteroscedasticity test, and Normality test are must have done.From those test above obtained the result are (1) Timing Difference and Permanent Difference Variable as partial has the signification influence to Taxable Income (2) Timing Difference and Permanent Difference Variable as simultan has the signification influence the Taxable Income.